Gifted education current perspectives and issues - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2014)
This volume addresses the most current perspectives and issues related to giftedness and is written by leaders in the field. An excellent resource for special educators, administrators, mental health clinicians, school counselors, and psychologists, this volume addresses the different educational issues that impact this population.
Legal issues in gifted education / Jaime A. Castellano, Michael S. Matthews -- Assessment of individuals who are gifted and talented / Frederick J. Brigham, Jeffrey P. Bakken -- Placement of students who are gifted / Elissa F. Brown, Tamra L. Stambaugh -- Giftedness as it relates to culturally and linguistically diverse students / Sunday O. Obi ... [et al.] -- Under-representation of African American and Hispanic students in gifted education : impact of social inequality, elitism, and colorblindness / Donna Y. Ford -- Inclusion and giftedness / Christina Borders, Stephanie Woodley, Elizabeth Moore -- Multicultural differentiated instruction for gifted students / Michelle Trotman Scott -- Effective practices and the development of talents in schools and classrooms / Ann Robinson, Debbie Dailey -- Technology and giftedness / Emily C. Bouck, Megan Hunley -- Recruiting and retaining gifted black students in STEM majors : implications for college counselors / Malik S. Henfield, Janice A. Byrd -- Families and gifted learners : developing talent and advocating for their own / Joy Lawson Davis.
Print version record
Keywords: Education -- Special Education -- Gifted; Education -- General; Teaching of gifted students; Teaching of specific groups & persons with special educational needs; Education; Special education; Gifted children